The Smoking Paradox: Impact of Smoking on Recanalization in the Setting of Intra-Arterial Thrombolysis - Meseguer, Elena (S. Karger AG, 2014)
BACKGROUND: The smoking paradox refers to a better outcome in smokers eligible for thrombolytic treatment in myocardial infarction or ischemic stroke. Recent findings suggest that current smokers may present higher recanalization rates after intravenous (IV) thrombolysis with recombinant tissue plasminogen activator (rt-PA). We evaluated the impact of smoking in a consecutive series of patients treated with intra-arterial (IA) rt-PA. METHODS: We analyzed data collected between April 2007 and December 2012 in our prospective registry. All acute ischemic stroke patients with an arterial occlusion treated by IA rt-PA (± IV, ± thrombectomy) were included. Arterial status was monitored with conventional angiography during the IA procedure. The primary study outcome was a complete recanalization achieved immediately after termination of IA rt-PA infusion. Secondary outcomes included complete recanalization after the end of the endovascular therapy (including complete recanalization achieved after adjunctive thrombectomy), favorable outcome (90-day modified Rankin Score ≤2), 90-day all-cause mortality, and any intracerebral hemorrhage. RESULTS: Among the 227 included patients, 18.5% (n = 42) were current smokers and 16.7% (n = 38) former smokers. Compared with nonsmokers, current smokers were younger, more often men, had less frequently hypertension, and cardioembolic etiology, whereas former smokers were more often men and had more frequently hypercholesterolemia. The rate of complete recanalization was 30% (n = 68) after IA rt-PA infusion and 49% after adjunctive thrombectomy. A higher complete recanalization rate was found both in current smokers (45.2%) and former smokers (42.1%) compared to nonsmokers (22.5%). After adjustment for potential confounders, the adjusted odds ratio (OR) for complete recanalization associated with ever-smokers was 2.51 [95% confidence interval (CI) 1.26-4.99; p = 0.009]. A similar adjusted OR was found when the complete recanalization achieved after thrombectomy was included (OR 2.18, 95% CI 1.13-4.19; p = 0.019). However, smoking status was not independently associated with favorable outcome (adjusted OR 1.41, 95% CI 0.62-3.22 for former smokers, and adjusted OR 1.35, 95% CI 0.59-3.05 for current smokers), 90-day all-cause mortality (adjusted OR 0.68, 95% CI 0.25-1.81 for former smokers, and adjusted OR 1.55, 95% CI 0.54-4.48 for current smokers) or intracerebral hemorrhage (adjusted OR 0.72, 95% CI 0.29-1.76 for former smokers, and adjusted OR 0.80, 95% CI 0.32-1.96 for current smokers). CONCLUSIONS: IA rt-PA administration was more effective to achieve complete arterial recanalization in current as well as former smokers. The characterization of the smoking paradox pathophysiology may lead to the identification of a patient-target population with a favorable response to rt-PA therapy. However, the smoking paradox should not be misinterpreted and not be used to promote smoking.